Analisis Pengaruh Kadar Air (Total Moisture) Batubara Terhadap Nilai Kalori Batubara di Front Penambangan - Doli Jumat Rianto (Formosa Journal of Multidisciplinary Research, 2022)
PT BRASU is a private company in the coal mining sector. Coal depositional environment below the earth's surface has different characteristics. The higher the water content, the lower the calorific value of coal. Methods of analysis in the form of Pearson's r test, regression test, and t test. The percentage of total moisture on the mine front is 21.37% (arb), with an average coal calorific value of 6537 cal/g. Based on the results of the Pearson r test, it was obtained at 0.950, the results of the regression test obtained the calorific value of coal of 6540.1 cal/g. While the t test obtained t_5,27> t_(3,182) shows a significant positive correlation (there is an effect) which is significant proximate quality on total moisture (TM) on the calorific value of coal in the mining front. The quality of coal that must be considered is to avoid mining when the soil is still wet after it rains.